Comparative analysis of time series of marine litter surveyed on beaches and the seafloor in the southeastern North Sea. (May 2015) - Schulz, Marcus; Krone, Roland; Dederer, Gabriele; Wätjen, Kai; Matthies, Michael
Abstract: The comparative analysis of marine litter in different marine compartments has rarely been attempted. In this study, long-term time series of marine litter abundance on the seafloor and on the coast, both from the southeastern North Sea, were analyzed for temporal trends and correlations. On four beach sections of 100 m length, mean abundances of total beach litter collected four times a year from 2002 to 2008 varied between 105 and 435 items. Mean densities of total inorganic litter on the seafloor amounted to 10.6 ± 9.7 kg km −2 in the offshore region (2001–2010) and 13.7 ± 12.6 kg km −2 in the Wadden Sea (1998–2007), respectively. In the offshore region, there was no significant long-term trend, while in the Wadden Sea, densities of marine litter declined significantly. Correlations between time series were weak, indicating different sources and transport processes responsible for compositions of beach litter and litter on the seafloor. Decreases in inputs from fisheries and substantial export due to resuspension are discussed as reasons for the decrease in litter on the seafloor in the Wadden Sea. Highlights: Bottom trawl data were analyzed for trends and correlations to beach litter data. In the Wadden Sea, densities of marine litter declined significantly. This is due to declining fisheries and substantial export due to resuspension. Accumulation zones of litter could not be detected due to episodic resuspension.